The effect of ICT use on the profitability of young agripreneurs in Malawi - Jolex, Aubrey; Tufa, Adane (MDPI, 2022)
The agricultural sector’s significant position in an economy and high potential benefits of agricultural transformation give developing countries major opportunities, especially for youth, to commercially start an agricultural enterprise. Increasing youth engagement in agriculture is fundamental for sustainably transforming agriculture and reducing youth unemployment. In achieving this, information and communication technologies hold great potential. Harnessing youth agribusiness opportunities through the use of ICT and its innovations are key to increasing profitability and providing employment. The study assesses the effect of the intensity of ICT use on profit using data collected from 317 young agripreneurs and an ordered logit model. The results show that profitability increases with the number of ICT tools used to receive and disseminate information relevant to agribusinesses. Therefore, relevant stakeholders should strive towards the implementation of programs that increase the number of ICT tools that can be used in agribusinesses.